2016
DOI: 10.1021/jacs.6b00307
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the P450 Oxygenation Cascade Involved in Glycopeptide Antibiotic Biosynthesis

Abstract: Glycopeptide antibiotics (GPAs) are nonribosomal peptides rich in modifications introduced by external enzymes. These enzymes act on the free peptide aglycone or intermediates bound to the nonribosomal peptide synthetase (NRPS) assembly line. In this process the terminal module of the NRPS plays a crucial role as it contains a unique recruitment platform (X-domain) interacting with three to four modifying Cytochrome P450 (P450) enzymes that are responsible for cyclizing bound peptides. However, whether these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
98
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(114 citation statements)
references
References 51 publications
14
98
0
2
Order By: Relevance
“…Recent work carried out by Cryle and coworkers has demonstrated the importance of the non-ribosomal peptide synthetase X-domain in helping to coordinate the P450-mediated oxidative cascade that leads to fully cyclized aglycones in the biosynthesis of vancomyin, teicoplanin, and other glycopeptides. 6971 While the P450 OxyB from the vancomycin pathway (OxyB van ) has long been recognized as a versatile biocatalyst with the ability to accept a wide range of peptidyl carrier protein (PCP)-bound substrates, 7275 the homolog from the teicoplanin pathway (OxyB tei , 74% sequence identity) exhibits a much narrower substrate scope when acting on PCP-bound peptides in the absence of the X-domain. 76 However, OxyB tei and homologs from other pathways are able to act on a broader range of substrates when the X-domain is present, although they tend to exhibit lower overall activity compared to OxyB van .…”
Section: Resultsmentioning
confidence: 99%
“…Recent work carried out by Cryle and coworkers has demonstrated the importance of the non-ribosomal peptide synthetase X-domain in helping to coordinate the P450-mediated oxidative cascade that leads to fully cyclized aglycones in the biosynthesis of vancomyin, teicoplanin, and other glycopeptides. 6971 While the P450 OxyB from the vancomycin pathway (OxyB van ) has long been recognized as a versatile biocatalyst with the ability to accept a wide range of peptidyl carrier protein (PCP)-bound substrates, 7275 the homolog from the teicoplanin pathway (OxyB tei , 74% sequence identity) exhibits a much narrower substrate scope when acting on PCP-bound peptides in the absence of the X-domain. 76 However, OxyB tei and homologs from other pathways are able to act on a broader range of substrates when the X-domain is present, although they tend to exhibit lower overall activity compared to OxyB van .…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, with the exception of OxyB van , the activity of Oxy enzymes in vitro has also been shown to be highly dependent on the presence of the X-domain fused to the peptidyl carrier protein domain [16]. This in turn has, for the first time, allowed the characterisation of the second cyclisation step, catalysed by OxyA, from the teicoplanin system [13,1617]. These results showed that OxyA, in contrast to OxyB, is highly selective for the correct stereochemistry of the peptide C-terminal residue and generally displays a higher selectivity for the structure of the substrate peptides [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…[250][251][252] More recent work has shown that the process of P450 recruitment to the NRPS-bound peptide is more complicated than is the case for PCP-bound amino acids, with GPA biosynthesis relying on the X-domain, a conserved (albeit modied) condensation domain found between the PCP 253 and TE-domains in the nal NRPS module. 243,[254][255][256][257] The X-domain has an interaction interface that specically binds to the Oxy enzymes, with these continually binding to and releasing from the X-domain to ensure that complete crosslinking of the peptide occurs. 254 The X-domain is also required in the majority of cases to support efficient P450-catalysed crosslinking in vitro, with this requirement strictly enforced for OxyA and OxyE that act aer OxyB.…”
mentioning
confidence: 99%
“…243,[254][255][256][257] The X-domain has an interaction interface that specically binds to the Oxy enzymes, with these continually binding to and releasing from the X-domain to ensure that complete crosslinking of the peptide occurs. 254 The X-domain is also required in the majority of cases to support efficient P450-catalysed crosslinking in vitro, with this requirement strictly enforced for OxyA and OxyE that act aer OxyB. 243,255,256,[258][259][260][261][262][263] Complestatin 264 and kistamicin 265 are structurally similar to GPAs, and also display several oxidative crosslinks whose generation has been ascribed to P450 enzymes, i.e.…”
mentioning
confidence: 99%